Synthesis and structural identification of fluorine‐18 labeled parathyroid hormone. (10th September 2015) - Yang, Yang; Richter, Susan; Wuest, Frank; Doschak, Michael R.
Abstract : Parathyroid hormone (PTH) is an 84 amino acid peptide hormone that plays a key role in bone and mineral metabolism. The biological actions of PTH are mediated via the N ‐terminal PTH(1–34) fragment, serving as the PTH receptor‐binding sequence, and which is therefore used clinically to treat conditions of low bone mass such as osteoporosis. In this study, PTH(1–34) was conjugated with non‐radioactive (stable F isotope) N ‐succinimidyl 4‐fluorobenzoate (SFB) leading to three isomeric mono ‐fluorobenzoated (FBz) PTH followed by Liquid chromatography‐Tandem mass spectrometry (LC‐MS/MS) assisted structural identification. Corresponding [ 18 F]SFB‐labeled PTH derivatives were prepared respectively and the Lys 13 site‐specific labeled [ 18 F]FBz PTH was isolated by HPLC with radiochemical purity >99% and specific activity of 2.78 GBq/µmol, suitable for future application with in vivo pharmacokinetic/pharmacodynamic studies of PTH, using preclinical Positron Emission Tomography Computed Tomography (PET/CT) imaging. Abstract : This is the synthesis and structural identification of F‐18 labeled parathyroid hormone (PTH)(1‐34), or PTH(1‐34). Here, we reacted PTH with [ 19 F]SFB resulting in three isomeric mono ‐species isolated by HPLC and characterized using liquid chromatography‐tandem mass spectrometry. Corresponding radiolabeling of PTH(1‐34) demonstrated same results. Desired [ 18 F]FBz‐PTH(Lys 13 ) was HPLC‐isolated with radiochemical purity >99%.